CURRENT TRENDS IN EFL SPEAKING INSTRUCTION - Sugiharto, M (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
ABSTRACT This article reviews the current practices in teaching EFL speaking, highlighting recent developments and identifying future trends in the field. It discusses key challenges faced in EFL speaking instruction, effective teaching methods, and the role of digital media in enhancing speaking skills. The article also examines psychological factors such as anxiety, motivation, and gender differences, and how these impact students' speaking performance. Using the state of the art method, the review synthesizes current research on pedagogical strategies like role-play, debates, and project-based learning, as well as the integration of platforms like TikTok and Flipgrid in language teaching. Based on this review, the article provides recommendations for EFL teachers and researchers, emphasizing the need for a supportive learning environment, the use of engaging materials, and the integration of technology to improve speaking proficiency among EFL learners. Keywords: EFL speaking, communicative competence, teaching methods, digital media, speaking anxiety, student motivation